Identification of 48 homologues of phosphatidylethanol in blood by LC-ESI-MS/MS - Gnann, Heike; Engelmann, C.; Skopp, Gisela; Winkler, M.; Auwärter, V.; Dresen, S.; Ferreirós, N.; Wurst, F. M.; Weinmann, W. (Analytical and bioanalytical chemistry, 2010)
Phosphatidylethanol (PEth) is an abnormal phospholipid carrying two fatty acid chains. It is only formed in the presence of ethanol via the action of phospholipase D (PLD). Its use as a biomarker for alcohol consumption is currently under investigation. Previous methods for the analysis of PEth included high-performance liquid chromatography (HPLC) coupled to an evaporative light scattering detector (ELSD), which is unspecific for the different homologues—improved methods are now based on time of flight mass spectrometry (TOF-MS) and tandem mass spectrometry (MS/MS). The intention of this work was to identify as many homologues of PEth as possible. A screening procedure using multiple-reaction monitoring (MRM) for the identified homologues has subsequently been established. For our investigations, autopsy blood samples collected from heavy drinkers were used. Phosphatidylpropanol 16:0/18:1 (internal standard) was added to the blood samples prior to liquid-liquid extraction using borate buffer (pH 9), 2-propanol and n-hexane. After evaporation, the samples were redissolved in the mobile phase and injected into the LC-MS/MS system. Compounds were separated on a Luna Phenyl Hexyl column (50 mm × 2 mm, 3 µm) by gradient elution, using 2 mM ammonium acetate and methanol/acetone (95/5; v/v). A total of 48 homologues of PEth could be identified by using precursor ion and enhanced product ion scans (EPI).